2013
DOI: 10.4081/hpr.2013.e17
|View full text |Cite
|
Sign up to set email alerts
|

Measuring health: related quality of life in hemodialysis patients. Psychometric properties of the Missoula-VITAS Quality of Life Index (MVQOLI-15) in Greece

Abstract: Different measuring tools have been used to understand the outcomes of end-stage renal disease (ESRD) therapies. However, survival, cost-effectiveness and quality of life (QOL) are the main parameters to evaluate treatment of ESRD. The current study meant to assess the psychometric properties (reliability and validity) of the Missoula-VITAS Quality of Life Index (MVQOLI-15) translation to Greek in patients undergoing hemodialysis (HD). A total sample of 79 HD patients voluntarily participated in this pilot stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
1
15
1
Order By: Relevance
“…Through the study of the psychometric properties of the PSEQ (Theofilou, 2014) and the study of the psychometric properties of the MVQOLI (Theofilou et al, 2013), their validity was found to be highly satisfactory. Also, the fact that almost all patients responded with eagerness and ease to the questionnaires shows that they are easy tools and appropriate for use in studies.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Through the study of the psychometric properties of the PSEQ (Theofilou, 2014) and the study of the psychometric properties of the MVQOLI (Theofilou et al, 2013), their validity was found to be highly satisfactory. Also, the fact that almost all patients responded with eagerness and ease to the questionnaires shows that they are easy tools and appropriate for use in studies.…”
Section: Discussionmentioning
confidence: 96%
“…The internal validity of the Greek version of the questionnaire was satisfactory with Cronbach's alpha of 0.74. (Theofilou et al, 2013).…”
Section: Data Collectionmentioning
confidence: 95%
See 1 more Smart Citation
“…The scale has been translated and validated into Greek. 14 , 15 MSPSS, which consists of 12 items, was developed by Zimet et al 16 to identify the social support factors perceived by the individuals. The scale is comprised of 3 groups depending on the source of support, each group consisting of 4 items.…”
Section: Methodsmentioning
confidence: 99%
“…The scale has been translated and validated into Greek. 14,15 The Pain Self-Efficacy Questionnaire (PSEQ) is a 10-item questionnaire developed to assess the confidence people with ongoing pain have in performing activities while in pain. It consists of two domains, physical and psychological.…”
Section: Instrumentsmentioning
confidence: 99%